Community Knowledge About Human Activities That Potential As A Disturbance Of The Ponda-Ponda Natural Reserve, East Luwu Regency - Witno Witno; Yumna Yumna; Eko Rifaldo; Andi Utami Batari Putri (Universitas Andi Djemma Palopo, 2023)
A nature reserve is a nature reserve area which because of its nature reserve has the uniqueness of plants, animals, and their ecosystems or certain ecosystems that need to be protected and their development takes place naturally. This research conducted in the ponda-ponda nature reserve is one of the conservation areas managed by the South Sulawesi KSDA Center which is located in East Luwu Regency. This study aims to analyze peope’s knowledge about human activities that have the potential to be a disturbance to the ponda-ponda nature reserve. Method of collecting data by making direct observations in the field with interview techniques using questionnaires. The population of this research is the Teromu village community and the sample who becomes the research respondent is 20 people. The data analysis used is descriptive socisl analysis. The results of this study area the knowledge of the community about human activities that have the potential to disrupt the Ponda-Ponda nature reserve, namely, 5% forest fires, 0% cultivation, 5% illegal grazing, 15% illegal logging, 30% wildlife hunting and 45% timber theft.